UFMylation: A supervisor of the HIF1α pathway and a potential therapeutic target for anti-PD-1 combination therapy in hypoxic tumors - Yongkang Zou; Zhaoxiang Wang; Qiang Jiang; Xia Kong; Xiaohe Ma; Zhengyan Liang; Zhiguo Wang; Beiying Chen; Jiao Yuan; Jiayue Wen; Sheng Ye; Yubin Yan; et al. (Proceedings of the National Academy of Sciences, 2025)
Activation of hypoxia signaling has been identified as an innate resistance signature against anti-PD-1 therapy, suggesting its potential as a target for combination treatments. Here, we demonstrate that UFMylation modification of HIF1α stabilizes the protein by antagonizing its ubiquitination and proteasomal degradation under hypoxic conditions. Mechanistically, depletion of UFL1 or defective UFMylation increases HIF1α binding to p53, promoting its degradation. Depletion of UFL1 or UBA5 , or defective UFMylation of HIF1α, destabilizes HIF1α, significantly inhibiting tumor growth and development in vitro and in xenograft mouse models. Defective UFMylation of HIF1α enhances the response to anti-PD-1 therapy in xenograft models. Clinically, UBA5 expression is upregulated in breast cancer tissues, and a selective UBA5 inhibitor reduces UFMylation activity and HIF1α protein levels, thereby enhancing anti-PD-1 combination therapy in mouse tumor models. Our findings highlight UFMylation as a critical posttranslational modification for the HIF1α pathway and a promising therapeutic target in hypoxic tumors.